Teknik Electroforming Tembaga Dalam Penciptaan Karya Kriya Logam - Aji Wiyoko (Institut Seni Indonesia Surakarta, 2010)
Creating metal work arts by electroforming technique is not common to do in Indonesia. Electroforming technique still opens in chances of arts creation in either two or three dimensional. This technique is save enough to the enviÂronment, so the writer combining the idea by presenting in working of art by Lucanus elaphus insect basic form. Composition ideas has purpose to get an art value about wisdom to the nature concept.Â Keyword: electroformingÂ